Welding flux composition and corresponding method for welding metals - Patents.com

JP7637254B2Active Publication Date: 2025-02-27ベルディシオ·ソリューションズ·ア·イ·エ
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2023549146
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-21
Publication Date
2025-02-27
Estimated Expiration
2040-10-21

AI Technical Summary

Benefits of technology

【0027】 溶接技術がレーザビームを伴う場合、フラックスは、レーザビームとのプラズマプルーム相互作用を改変する。特に、フラックスの溶解による酸素の増加は、レーザビームの散乱を低下させる。その結果、レーザスポット径が縮小される一方で、キーホール効果が増強される。これにより、エネルギービームはさらに深く浸透し、接合部に極めて効率的に送達されることが可能になる。これは、溶接溶け込みを増加させ、熱影響域を最小化し、次いで、これは部分の歪みを制限する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007637254000001
    Figure 0007637254000001
  • Figure 0007637254000002
    Figure 0007637254000002
  • Figure 0007637254000003
    Figure 0007637254000003
Patent Text Reader

Abstract

The present invention relates to a welding flux comprising a titanate and a nanoparticulate niobium compound selected from niobium oxide, alkali niobates, and mixtures thereof.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the welding of metal substrates, in particular when at least one of the metal substrates is a steel substrate. The present invention also relates to the composition of a welding flux used to improve the quality of the weld. The welding flux can be included in a solution that is applied topically on the steel substrate to form a pre-coating or in a flux-cored wire that is used as an alternative to a pre-coating. The present invention also relates to a corresponding method for the manufacture of a welded joint. The present invention is particularly well suited for the construction, shipbuilding, transport industry (railroad and automotive), energy-related structures, oil and gas and offshore industries. [Background technology]

[0002] It is well known to weld metallic substrates using different welding techniques such as Gas Metal Arc Welding (GMAW), Gas Tungsten Arc Welding (GTAW), also known as Tungsten Inert Gas Welding (TIGW), Submerged Arc Welding (SAW), Laser Beam Welding (LBW), Narrow Gap Welding, also known as Narrow Gap Welding, Laser-Arc Hybrid Welding, etc. Welding can be performed with the help of a welding flux to increase the penetration in the substrate. This welding flux is different from the shielding flux, which may be mainly used to protect the welded zone from oxidation during welding.

[0003] It is also known to use a filler wire to weld metal substrates, especially when gaps must be filled. The filler wire can deliver the weld from the side (as in gas tungsten arc welding and laser welding), or the filler wire can be a consumable electrode (as in submerged arc welding, gas metal arc welding, gas shielded flux cored arc welding, narrow gap welding, and hybrid laser welding where the arc head is a gas metal arc). In some cases, the filler wire is in the form of a flux cored wire, i.e., a wire that is hollow and filled with flux containing components that improve performance.

[0004] Patent application WO 00 / 16940 discloses that deep penetration gas tungsten arc welding is achieved using titanates such as Na2Ti3O7 or K2TiO3. To provide deep penetration welds in carbon steels, chromium-molybdenum steels, stainless steels and nickel-based alloys, the titanates are added to the molten pool as part of the welding flux or as part of the filler wire. The titanate compounds of WO 00 / 16940 are used in the form of high purity powders of about 325 mesh or finer, 325 mesh corresponding to 44 μm. Various additional components may be optionally added to the titanate-based filler wire, including transition metal oxides such as TiO, TiO2, Cr2O3 and Fe2O3, silicon dioxide, manganese silicides, fluorides and chlorides, to control the arc wander, bead consistency and the slag and surface appearance of the weld. All compounds of the flux have micrometer dimensions.

[0005] Although the fluxes disclosed in WO 00 / 16940 improve penetration, the penetration is not optimal for steel substrates. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] International Publication No. 2000 / 16940 Summary of the Invention [Problem to be solved by the invention]

[0007] Thus, a need exists to improve the weld penetration in steel substrates and therefore the mechanical properties of the welded steel substrates. There is also a need to increase the deposition rate and productivity of the weld. [Means for solving the problem]

[0008] To this end, the present invention relates to a welding flux comprising a titanate and a nanoparticulate niobium compound selected from among niobium oxide, alkali niobates and mixtures thereof.

[0009] The weld according to the invention may also have any of the features listed below, considered individually or in combination:

[0010] the nanoparticulate niobium compounds are selected from NbO, NbO2 and Nb2O5 and mixtures thereof; The proportion of nanoparticle niobium compounds in the flux is 80% by weight or less; The proportion of nanoparticle niobium compounds in the flux is between 2 and 30% by weight. The nanoparticles of nanoparticulate niobium have a size comprised between 5 and 150 nm; the titanates are selected from among Na2Ti3O7, NaTiO3, K2TiO3, K2Ti2O5, MgTiO3, SrTiO3, BaTiO3, CaTiO3, FeTiO3 and ZnTiO4 and mixtures thereof; The proportion of titanate in the flux is 45% by weight or more. The diameter of the titanate is between 1~40μm, The welding flux further comprises at least one additional nanoparticulate oxide selected from TiO2, SiO2, ZrO2, Y2O3, Al2O3, MoO3, CrO3, CeO2, La2O3 and mixtures thereof; the welding flux further comprises a particulate compound selected from among particulate oxides and / or particulate fluorides, The welding flux further comprises a particulate compound selected from the list consisting of CeO2, Na2O, Na2O2, NaBiO3, NaF, CaF2, cryolite (Na3AlF6) and mixtures thereof; The welding flux further comprises a solvent; The welding flux contains 1-200g / L of nanoparticle niobium compound; The welding flux contains 100-500g / L of titanate. The welding flux further comprises a binder precursor.

[0011] The present invention also relates to a method for the production of a pre-coated steel substrate comprising the step of at least partially depositing the welding flux of the present invention onto a steel substrate.

[0012] The present invention also relates to a pre-coated steel substrate obtainable by the method of the present invention, at least partially coated with a pre-coating comprising a titanate and a nanoparticulate niobium compound selected from among niobium oxide, alkali niobates and mixtures thereof.

[0013] The present invention relates to a method for the manufacture of a welded joint, comprising the following successive steps: I. Providing at least two metal substrates, at least one of which is a pre-coated steel substrate of the present invention; and II. welding the at least two metal substrates; The present invention also relates to a method, comprising:

[0014] The present invention also relates to a flux cored wire comprising the flux of the present invention.

[0015] The invention also relates to a method for the production of a welded joint comprising arc welding or laser welding to steel materials with a flux cored wire according to the invention.

[0016] The present invention relates to a method for the manufacture of a welded joint, comprising the following successive steps: I. Providing at least two metal substrates, at least one of the metal substrates being a steel substrate; II. applying a welding flux of the present invention onto the at least two metal substrates in front of the welding head simultaneously with the welding of the at least two metal substrates by the welding head; The present invention also relates to a method, comprising:

[0017] The following terms are defined:

[0018] Nanoparticles are particles between 1 and 200 nanometers (nm) in size. The term "nanoparticles" refers to compounds in the form of nanoparticles in the above range.

[0019] Titanates refer to inorganic compounds that contain titanium, oxygen and at least one additional element, such as an alkali metal element, an alkaline earth element, a transition metal element or a metallic element, which may be in the form of their salts.

[0020] "Coated" means that the steel substrate is at least locally covered with a pre-coating. The covering can be limited, for example, to the area where the steel substrate is to be welded. "Coated" is inclusive of "directly on" (without intermediate materials, elements or spaces disposed therebetween) and "indirectly on" (with intermediate materials, elements or spaces disposed therebetween). For example, coating a steel substrate can include applying a pre-coating directly on the substrate without an intermediate material / element therebetween, and applying a pre-coating indirectly on the substrate with one or more intermediate materials / elements therebetween (such as an anti-corrosion coating).

[0021] Without being bound by any theory, it is believed that the welding flux and the corresponding pre-coating and flux cored wire primarily modify the physics of the molten pool. In the present invention, it is believed that the nature of the compounds as well as the size of the oxide particles, which is 100 nm or less, modify the physics of the molten pool.

[0022] In fact, the flux is melted and incorporated into the molten metal in the form of dissolved species and, if the welding technique involves an arc, into the arc in the form of ionized species, which are caused to converge by the presence of the titanate and nanoparticulate niobium compounds in the arc.

[0023] Additionally, fluxes dissolved in molten metal modify Marangoni flow, which is mass transfer at a liquid-gas interface due to surface tension gradients. In particular, the components of the flux modify the surface tension gradient along the interface. This modification of surface tension results in a reversal of the fluid flow toward the center of the weld pool. This reversal results in improved weld penetration and efficiency, increasing the deposition rate and therefore productivity. Without being bound by any theory, it is believed that nanoparticles dissolve at a lower temperature than fine particles, thus dissolving more oxygen into the molten pool and activating the reverse Marangoni flow.

[0024] When the welding technique involves an arc, the effect of the reverse Marangoni flow, combined with the higher plasma temperature due to the arc convergence, further improves the weld penetration and material deposition rate. When the welding technique involves a laser beam, the reverse Marangoni flow contributes to maintaining the proper keyhole shape, which in turn prevents gas entrapment and therefore porosity in the weld.

[0025] Additionally, the dissolved oxygen acts as a surfactant, improving the wetting of the molten metal on the base metal, thus avoiding serious defects that tend to appear in welds, such as lack of edge fusion.

[0026] Additionally, as the components of the flux increase surface tension with temperature, the wetting of the weld material increases along the cooler edges of the molten pool than in the center, which prevents slag entrapment.

[0027] When the welding technique involves a laser beam, the flux modifies the plasma plume interaction with the laser beam. In particular, the increase in oxygen due to the melting of the flux reduces the scattering of the laser beam. As a result, the laser spot diameter is reduced while the keyhole effect is enhanced. This allows the energy beam to penetrate deeper and be delivered to the joint very efficiently. This increases the weld penetration and minimizes the heat affected zone, which in turn limits distortion of the part.

[0028] The invention will be better understood on reading the following description, which is provided purely for illustrative purposes and is not intended to be limiting in any way. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] The present invention relates to the welding of steel substrates. Preferably, the steel substrate is carbon steel.

[0030] The steel substrate may optionally be coated on at least a portion of one of its faces with an anticorrosive coating, preferably comprising a metal selected from the group consisting of zinc, aluminum, copper, silicon, iron, magnesium, titanium, nickel, chromium, manganese and alloys thereof.

[0031] In a preferred embodiment, the anticorrosive coating is an aluminum-based coating containing less than 15% Si, less than 5.0% Fe, optionally 0.1-8.0% Mg, and optionally 0.1-30.0% Zn, with the remainder being Al and unavoidable impurities arising from the manufacturing process. In another preferred embodiment, the anticorrosive coating is a zinc-based coating containing 0.01-8.0% Al, optionally 0.2-8.0% Mg, with the remainder being Zn and unavoidable impurities arising from the manufacturing process.

[0032] The anticorrosive coating is preferably applied to both sides of the steel substrate.

[0033] The steel can be welded to a steel substrate of the same or different composition. The steel can also be welded to another, for example aluminium.

[0034] The welding flux comprises a titanate and a nanoparticulate niobium compound selected from among niobium oxide, alkali niobates, and mixtures thereof. In other words, the precoating comprises a titanate and at least one nanoparticulate niobium compound, and the at least one nanoparticulate niobium compound is selected from the group consisting of niobium oxide, alkali niobates, and mixtures thereof. This means that the precoating does not comprise any other nanoparticulate niobium compounds than those listed.

[0035] The titanate is selected from the group of titanates consisting of alkali metal titanates, alkaline earth metal titanates, transition metal titanates, metal titanates, and mixtures thereof. More preferably, the titanate is selected from among Na2Ti3O7, NaTiO3, K2TiO3, K2Ti2O5, MgTiO3, SrTiO3, BaTiO3, CaTiO3, FeTiO3, and ZnTiO4, and mixtures thereof. It is believed that these titanates further increase the penetration depth based on the effect of reverse Marangoni flow. It is the inventors' understanding that all titanates behave somewhat similarly and increase the penetration depth. Thus, all titanates are part of the present invention. Those skilled in the art will know which titanate must be selected depending on the specific case. To do so, they will take into account how easily the titanate melts and dissolves, how much the titanate increases the dissolved oxygen content, and how the additional elements of the titanate affect the physics of the molten pool and the microstructure of the final weld. For example, NaTiO7 is preferred due to the presence of Na which improves slag formation and desorption.

[0036] Preferably, the titanate has a diameter between 1 and 40 μm, more preferably between 1 and 20 μm, advantageously between 1 and 10 μm. This diameter of the titanate is believed to further improve the arc convergence and the inverse Marangoni effect. Furthermore, having small micrometer titanate particles increases the specific surface area available for mixing with the nanoparticulate niobium compound, further adhering the nanoparticulate niobium compound to the titanate particles.

[0037] Preferably, the weight percentage of titanate in the dry weight of the welding flux is equal to or greater than 45%, more preferably between 45% and 90%, even more preferably between 55% and 87%.

[0038] The nanoparticulate niobium compounds are selected from niobium oxide, alkali niobates and mixtures thereof. The niobium oxides can be selected in particular from NbO, NbO2 and Nb2O5. The alkali niobates can be selected in particular from LiNbO3, NaNbO3 and KNbO3. These nanoparticles dissolve easily in the molten pool and provide oxygen to the molten pool, thus improving the wettability and material deposition and allowing deeper weld penetration. In contrast to other oxides such as CaO, MgO, B2O3, Co3O4 or Cr2O3, they do not tend to form brittle phases, do not have a high refractory effect that prevents the heat from melting the steel correctly and their metal ions do not tend to recombine with the oxygen in the molten pool. Moreover, they pose less health and safety concerns than other nanoparticulate oxides and can therefore very efficiently replace some of the other nanoparticulate oxides and even improve the results.

[0039] The nanoparticulate niobium compound is preferably Nb2O5 since it has the highest oxygen content, is stable, and is readily available at a reasonable cost.

[0040] Preferably, the nanoparticles of the nanoparticulate niobium compound have a size comprised between 5 and 150 nm, more preferably between 50 and 150 nm.

[0041] The welding flux may further comprise at least one additional nanoparticulate oxide selected from TiO2, SiO2, ZrO2, Y2O3, Al2O3, MoO3, CrO3, CeO2, La2O3 and mixtures thereof, which also dissolve easily in the molten pool to further improve wettability, material deposition and weld penetration.

[0042] Preferably, the additional nanoparticulate oxide is SiO2, which further increases the depth of penetration and facilitates slag removal.

[0043] Examples of mixtures of additional nanoparticulate oxides include: Yttria-stabilized zirconia (YSZ), a ceramic in which the cubic crystal structure of zirconium dioxide (ZrO2) is stabilized at room temperature by adding yttrium oxide (Y2O3); A 1:1:1 combination of La2O3, ZrO2 and Y2O3, which helps adjust the refractory effect and promotes the formation of inclusions.

[0044] Preferably, the nanoparticles of the additional nanoparticulate oxide have a size comprised between 1 and 100 nm, more preferably between 5 and 60 nm, this nanoparticle diameter being believed to further improve the homogeneous distribution of the flux.

[0045] Preferably, the weight percentage of nanoparticles in the dry weight of the welding flux (niobium compound alone or in combination with other nanoparticle oxides) is less than or equal to 80%, preferably between 2 and 50%, more preferably between 10 and 40%. More preferably, the weight percentage of nanoparticle niobium compound in the dry weight of the welding flux is comprised between 2 and 30%. More preferably, the weight percentage of additional nanoparticle oxides in the dry weight of the welding flux, if present, is comprised between 5 and 20%.

[0046] According to another variation of the invention, the flux further comprises particulate compounds such as particulate oxides and / or particulate fluorides, such as Na2O, Na2O2, CeO2, NaBiO3, NaF, CaF2, cryolite (Na3AlF6). For some of the nanoparticulate oxides listed above, the transition from nanoparticles to fine particles reduces health and safety concerns associated with the use of some of these oxides. Na2O, Na2O2, NaBiO3, NaF, CaF2, cryolite can be added to improve slag formation so that slag entrapment is further prevented. They also help to form an easily separable slag. The flux can comprise 0.1-5% by weight of Na2O, Na2O2, NaBiO3, NaF, CaF2, cryolite or mixtures thereof, based on the dry weight of the welding flux.

[0047] According to one embodiment of the present invention, the flux is contained in the sheath of the flux cored wire. Such a configuration is particularly advantageous compared to the application of the same composition as a pre-coating on the substrate to be welded. First of all, the extra step of coating the substrate before welding is suppressed. Furthermore, there is no need to remove excess pre-coating along the weld after welding. In this regard, the particles provided by the flux cored wire are also used more efficiently, since they all dissolve in the molten pool. Finally, solvents and spray mists during the coating process are avoided, which is beneficial for the health and safety of the workers.

[0048] According to one variant of the invention, the flux in the flux cored wire consists of a titanate and a nanoparticulate niobium compound.

[0049] According to another variant of the invention, the flux in the flux cored wire may further comprise iron powder as a remainder, which may represent up to 55% by weight of the flux.

[0050] In the present invention, the material of the sheath is not particularly limited. The material of the sheath can be steel, for example, copper-clad C-Mn steel.

[0051] The wires usually have a diameter comprised between 0.8 mm and 4 mm. As for the sheath, its thickness varies according to the selected percent fill. The percent fill is the ratio of the weight of the flux components or "fill" compared to the total weight of the wire.

[0052] Regarding the process, in a first step, the titanate and the nanoparticulate niobium compound are preferably mixed. This can be done either under wet conditions, using a solvent such as acetone, or under dry conditions, for example in a 3D powder shaker mixer. The mixing promotes a strong agglomeration of the nanoparticles on the titanate particles, which prevents the unintentional release of the nanoparticles into the air, which is a health and safety problem. In a second step, the flux thus obtained is deposited on a thin, narrow strip that in the previous step passed through a forming roll to form a strip of U-shaped cross section. The flux-filled U-shaped strip then flows through a special closing roll, which forms the flux-filled U-shaped strip into a tube and tightly compresses the core material. This tube is then pulled through a wire drawing die in order to reduce its diameter and further compress the core material. The pulling tightly seals the sheath and also fixes the core material inside the tube under compression, thus avoiding discontinuities in the flux.

[0053] Once the flux cored wire according to the invention is provided, a welded joint can be produced by arc welding or laser welding the flux cored wire to steel materials. The type of welding technique is not limited, as long as it is compatible with the flux cored wire according to the invention and is used as a filler wire to deliver the weld from the side (as in gas tungsten arc welding and laser welding) or as a consumable electrode (as in submerged arc welding, gas metal arc welding, gas shielded flux cored arc welding, narrow gap welding and hybrid laser welding where the arc head is gas metal arc). Depending on the welding technique, the welded zone can be covered by a shielding flux. The shielding flux protects the welded zone from oxidation during welding.

[0054] According to another embodiment of the present invention, the above-mentioned flux is applied at least partially onto a steel substrate to form a pre-coating.

[0055] In this case, the flux may advantageously further comprise a solvent, which allows a well-dispersed pre-coating. Preferably, the solvent is volatile at ambient temperature. For example, the solvent is selected from among volatile organic solvents such as water, acetone, methanol, isopropanol, ethanol, ethyl acetate, diethyl ether, and non-volatile organic solvents such as ethylene glycol.

[0056] In particular, flux containing a solvent should be 100 to 500 g / L, and more preferably 175 to 250 g / L. -1 In particular, fluxes containing solvents are used in amounts between 1 and 200 g.L. -1 , more preferably 5 to 80 g.L -1 Thanks to these concentrations of titanate and nanoparticulate niobium compound, the quality of the welds obtained with the help of a corresponding pre-coating is further improved.

[0057] According to one variant of the invention, the flux further comprises a binder precursor to embed the titanate and nanoparticulate niobium compounds and to improve the adhesion of the precoating on the steel substrate. Preferably, the binder precursor is a sol of at least one organofunctional silane. Examples of organofunctional silanes are silanes functionalized in particular with groups from the amine, diamine, alkyl, amino-alkyl, aryl, epoxy, methacryl, fluoroalkyl, alkoxy, vinyl, mercapto and aryl families. Preferably, the binder precursor is present in an amount of 40 to 400 g.L of the precoating solution. -1 is added in an amount of

[0058] Regarding the process, in the first step, the titanate and the nanoparticulate niobium compound are preferably mixed. This can be done either in wet conditions using a solvent such as acetone or in dry conditions, for example in a 3D powder shaker mixer. The mixing promotes strong agglomeration of the nanoparticles on the titanate particles, which prevents unintentional release of the nanoparticles into the air, which is a health and safety issue. In the second step, the flux is applied at least partially onto the steel substrate to form a precoating.

[0059] The deposition of the flux can especially be carried out by spin coating, spray coating, dip coating or brush coating.

[0060] Preferably, the flux is only locally deposited. In particular, the flux is applied to the area where the steel substrates are to be welded. The flux can be present on the edge of the steel substrates to be welded, on one part of one side of the substrates to be welded on one sidewall or on one bevel edge, if present.

[0061] Once the flux has been applied onto the steel substrate, the pre-coating solution can optionally be dried. Drying can be accomplished by blowing with air or an inert gas at ambient or elevated temperatures. If the flux contains a binder, the drying step is preferably also a curing step during which the binder is cured. Curing can be accomplished by infrared (IR), near infrared (NIR), or a conventional oven.

[0062] Preferably, no drying step is performed if the solvent is volatile at ambient temperature, in which case the solvent evaporates, resulting in a pre-coating on the steel substrate.

[0063] According to one variant of the invention, a pre-coating is formed on a steel substrate and, once dried, the pre-coating consists of a titanate and a nanoparticulate niobium compound.

[0064] According to another variant of the invention, the precoating further comprises at least one binder that embeds the titanate and nanoparticulate niobium compounds and improves the adhesion of the precoating on the steel substrate. This improved adhesion further prevents the particles of the precoating from being blown away by the flow of shielding gas, if a shielding gas is used. Preferably, the binder is purely inorganic, in order to avoid toxic gases that organic binders may generate, especially during welding. Examples of inorganic binders are organofunctional silanes or siloxane sol-gels. Examples of organofunctional silanes are silanes functionalized in particular with groups from the amine, diamine, alkyl, amino-alkyl, aryl, epoxy, methacryl, fluoroalkyl, alkoxy, vinyl, mercapto and aryl families. Aminoalkylsilanes are particularly preferred, as they greatly promote adhesion and have a long shelf life. Preferably, the binder is added in an amount of 1 to 20% by weight of the precoating.

[0065] Preferably, the thickness of the pre-coating is between 10 and 140 μm, more preferably between 30 and 100 μm.

[0066] Once the pre-coating is formed on a portion of the steel substrate, this portion can be welded to another metal substrate. The type of welding technique is not limited. The welding technique can be, for example, gas metal arc welding (GMAW), gas tungsten arc welding (GTAW), also known as tungsten inert gas welding (TIGW), submerged arc welding (SAW), laser beam welding (LBW), narrow gap welding, also known as narrow groove welding, or laser-arc hybrid welding.

[0067] According to another embodiment of the invention, the above mentioned welding flux is applied directly onto the metal substrate during welding, in particular to the weld zone.

[0068] In particular, the welding flux is applied at least partially simultaneously on the two metal substrates while they are being welded. The welding flux is applied in front of the welding device, in particular in front of the welding head. The welding head refers here to an electrode or a laser head, either consumable or non-consumable, that generates an arc, depending on the welding technique. Thus, when the energy applied through the welding head strikes a portion of the substrate covered with the welding flux, the components of the welding flux are melted and dissolved in the molten pool. The dissolved titanate and nanoparticulate niobium compounds have the above-mentioned effects.

[0069] The welding flux is preferably applied to a portion of the metal substrate immediately prior to the portion being subjected to the energy applied via the welding head.

[0070] Preferably, the welding flux is applied along the edges of the metal substrates to be welded in a width at least equal to the weld width so that the welding flux is efficiently dissolved into the molten pool.

[0071] Preferably, the welding flux is stored in a flux hopper, which is located in front of the welding apparatus, particularly in front of the weld head, and moves therewith. During welding, the hopper deposits the welding flux onto a small portion of the metal substrate in front of the weld head. The flux hopper controls the rate of flux deposition.

[0072] In one variant of the invention, the welding flux is applied on the two metal substrates before applying the shielding flux. In front of the welding head, there is first a flux hopper storing the shielding flux, and then a flux hopper storing the welding flux. In other words, the welding flux hopper is further forward of the welding head than the shielding flux hopper. As a result, the welding flux is applied at a first location on the metal substrate, and the shielding flux is applied at a second location to cover the welding flux. Thus, the welded zone is protected from oxidation during welding. From a process point of view, both the application of the welding flux and the application of the shielding flux are simultaneous with the welding.

[0073] In another variant of the invention, the welding flux is also a shielding flux. The welding flux preferably comprises lime, silica, manganese oxide and calcium fluoride in the form of particles of micrometer and / or millimeter size. These compounds provide the flux with a shielding effect in addition to the effect provided by the titanates and nanoparticulate niobium compounds. The welded zone is therefore protected from oxidation during welding.

[0074] In that case, the titanate and nanoparticulate niobium compounds are mixed at an earlier stage with additional components such as lime, silica, manganese oxide and calcium fluoride in the form of micrometer and / or millimeter sized particles, and the mixture is then applied onto the two metal substrates, preferably by means of a flux hopper.

[0075] The type of welding technique to be used in this embodiment of the invention is not limited, and may be, for example, gas metal arc welding (GMAW), gas tungsten arc welding (GTAW), also known as tungsten inert gas welding (TIGW), submerged arc welding (SAW), laser beam welding (LBW), narrow gap welding, also known as narrow groove welding, or laser-arc hybrid welding.

[0076] Even so, the variants in which the welding flux is also a shielding flux are particularly advantageous for welding techniques that use a shielding flux, such as submerged arc welding (SAW), narrow gap welding based on submerged arc welding and laser-arc hybrid welding based on submerged arc welding.

[0077] Finally, the present invention relates to the use of the welding flux according to the invention, of the corresponding pre-coating or of the corresponding flux cored wire, for example for the manufacture of pressure vessels, offshore and oil and gas parts, shipbuilding, automotive, nuclear reactor parts and heavy industry and manufacturing in general. EXAMPLES

[0078] [Example 1] Narrow Gap Welding: A steel substrate was selected having the chemical composition in weight percent disclosed in Table 1:

[0079] [Table 1]

[0080] The steel substrate was 50 mm thick. The steel substrate had a tensile strength of 470-630 MPa and a yield strength of 335 MPa.

[0081] Samples of 100 x 150 mm were prepared with side walls having a 0° bevel. The side walls to be welded were cleaned from oil and dirt with acetone.

[0082] Sample 1 was not coated with a precoat.

[0083] For sample 2, an acetone solution containing MgTiO3 (diameter: 2 μm), Nb2O5 (diameter: 100 nm) and SiO2 (diameter: 10 nm) was prepared by mixing acetone with the following elements: In the acetone solution, the concentration of MgTiO3 was 175 g.L -1 and the concentration of Nb2O5 is 50 g.L -1 and the concentration of SiO2 is 25 g.L -1 The cleaned sidewall of sample 2 was then coated with an acetone solution by spraying. The acetone was allowed to evaporate. The percentage of MgTiO3 in the pre-coating was 70 wt%, the percentage of Nb2O5 was 20 wt%, and the percentage of SiO2 was 10 wt%. The pre-coating was 50 μm thick.

[0084] For sample 3, an acetone solution containing MgTiO3 (diameter: 2 μm), Nb2O5 (diameter: 100 nm), SiO2 (diameter: 10 nm), a premixed 1:1:1 combination of La2O3, ZrO2, and Y2O3 (diameters: 50, 40, and 40 nm, respectively), and NaBiO3 (diameter: 1.5 μm) was prepared by mixing acetone with the following elements: In the acetone solution, the concentration of MgTiO3 was 187.5 gL -1 and the concentration of Nb2O5 is 25 g.L -1 and the concentration of SiO2 is 25 g.L -1 and the concentration of the additional nanoparticle oxide was 0.125 g L -1 and the concentration of NaBiO3 is 12.38 g L -1 The pre-coating was 50 μm thick. The cleaned sidewall of sample 3 was then coated with an acetone solution by spraying. The acetone was allowed to evaporate. The percentage of MgTiO3 in the pre-coating was 75 wt%, the percentage of Nb2O5 was 10 wt%, the percentage of SiO2 was 10 wt%, the percentage of additional nanoparticulate oxides was 0.05 wt%, and the percentage of NaBiO3 was 4.95 wt%. The pre-coating was 50 μm thick.

[0085] Samples 1-3 were each placed side-by-side with a bare sample of the selected steel substrate separated by a 13 mm gap and welded by narrow gap gas metal arc welding by performing weld passes until the bevel was filled and the joint was completed. The welding parameters are listed in Table 2 below.

[0086] [Table 2]

[0087] The composition of the consumable electrodes used in all cases is given in Table 3 below.

[0088] [Table 3]

[0089] Sample 1 was welded with 12 passes, whereas samples 2 and 3 were welded with 10 passes. This first result already shows that the pre-coating according to the invention increases the deposition rate and productivity of narrow gap welds.

[0090] Improved wetting of the weld metal on the bevel surface was also observed in Samples 2 and 3 compared to Sample 1.

[0091] After narrow gap welding, the welds of all welded assemblies were first inspected visually and then ultrasonically (both linear and volumetric). The welds were also analyzed visually and microscopically, especially by Liquid Penetrant Inspection (LPI).

[0092] The results are summarized in Table 4 below.

[0093] [Table 4]

[0094] The results show that a pre-coating on the sidewall of the steel substrate improves narrow gap welding.

[0095] [Example 2] Flux cored wire: Three fluxes were prepared and introduced into a 0.5 mm C-Mn steel sheath to form a wire with a diameter of 1.6 mm. Their compositions were: Flux 1: 85 wt.% MgTiO3 (diameter 2 μm), 10 wt.% SiO2 (diameter range: 12-23 nm) and 5 wt.% Nb2O5 (diameter range: 100 nm), Flux 2: 70 wt.% MgTiO3 (diameter 2 μm), 10 wt.% SiO2 (diameter range: 12-23 nm) and 20 wt.% Nb2O5 (diameter range: 100 nm); Flux 3: 68.5 wt.% MgTiO3 (diameter: 2 μm), 10 wt.% SiO2 (diameter range: 12-23 nm), 20 wt.% Nb2O5 (diameter range: 100 nm), 1 wt.% Na3AlF6 and 0.5 wt.% CeO2 (diameter: ≦5 μm) It was.

[0096] The corresponding flux cored wires identified as Samples 4, 5 and 6 respectively were tested during bead-on-plate gas tungsten arc welding at an intensity of 110A and voltages between 10.8-12.8V on structural steel (C-Mn S355) whose composition is detailed in Table 5 below.

[0097] [Table 5]

[0098] During these tests, samples 4, 5 and 6 were compared to the following commercially available wires:

[0099] Outershield® MC710-H, a mild steel metal cored wire supplied by Lincoln Electric®, whose sheath is filled with iron powder (Sample 7).

[0100] OK Tubrodur 15CrMn O / G (Sample 8), a flux cored wire supplied by ESAB® and used for mild steel, low alloy steel and C-Mn steel. The exact composition of the flux is unknown.

[0101] The results obtained using 500 mm wire are detailed in Table 6.

[0102] [Table 6]

[0103] The results show that there is simultaneously a significant increase in welding speed and a significant increase in material deposition.

[0104] Additionally, the width of the deposited material was measured and compared. The welds obtained using Samples 4, 5 and 6 appeared to be, on average, 18% larger than the welds obtained using Sample 7 and 24% larger than the welds obtained using Sample 8.

[0105] The components of the flux according to the present invention exhibit a surface tension that decreases with temperature such that the wetting of the weld material increases along the edge of the molten pool.

[0106] [Example 3] Gas Tungsten Arc Welding (GTAW): For this example, a steel substrate was used having the chemical composition in weight percent disclosed in Table 7:

[0107] [Table 7]

[0108] The steel substrate was 5.5 mm thick.

[0109] For sample 9, an ethyl acetate solution containing MgTiO3 (diameter: 2 μm), SiO2 (diameter range: 10 nm), and Nb2O5 (diameter range: 100 nm) was prepared by mixing ethyl acetate with the following elements: In the ethyl acetate solution, the concentration of MgTiO3 was 175 g.L -1 and the concentration of SiO2 is 25 g.L -1 and the concentration of Nb2O5 is 50 g.L -1 The ethyl acetate solution was sprayed onto the steel substrate over an area larger than the weld to be performed. The ethyl acetate was allowed to evaporate. The proportion of MgTiO3 in the precoating was 70% by weight, the proportion of SiO2 was 10% by weight, and the proportion of Nb2O5 was 20% by weight.

[0110] For sample 10, an aqueous solution was prepared containing the following components: 363 g.L -1 of MgTiO3 (diameter: 2 μm), 77.8 g L -1 of SiO2 (diameter range: 12-23 nm), 77.8 g L -1 of Nb2O5 (diameter range: 100 nm) and 238 g.L -1 of 3-aminopropyltriethoxysilane (Dynasylan® AMEO manufactured by Evonik®). The solution was applied onto a steel substrate and dried by 1) IR and 2) NIR.

[0111] The dried pre-coating was 40 μm thick and contained 62 wt % MgTiO 3 , 13 wt % SiO 2 , 13 wt % Nb 2 O 5 and 12 wt % binder derived from 3-aminopropyltriethoxysilane.

[0112] For sample 11, an aqueous solution was prepared containing the following components: 330 g.L -1 of MgTiO3 (diameter: 2 μm), 70.8 g L -1 of SiO2 (diameter range: 12-23 nm), 70.8 g L -1 of Nb2O5 (diameter range: 100 nm), 216 g.L -1of 3-aminopropyltriethoxysilane (Dynasylan® AMEO manufactured by Evonik®) and 104.5 gL -1 A composition of organofunctional silane and functionalized nanoscale SiO2 particles (Dynasylan® Sivo 110 manufactured by Evonik). The solution was applied onto a steel substrate and dried by 1) IR and 2) NIR. The dried pre-coating was 40 μm thick and contained 59.5 wt. % MgTiO3, 13.46 wt. % SiO2, 12.8 wt. % Nb2O5 and 14.24 wt. % binder obtained from 3-aminopropyltriethoxysilane and organofunctional silane.

[0113] For Sample 9, spraying was easy and the pre-coating was uniform, confirming that ethyl acetate can easily replace acetone in solvent-based flux formulations.

[0114] For samples 10 and 11, the adhesion of the precoating on the steel substrate was significantly improved compared to sample 9.

[0115] Gas tungsten arc welding was then performed on Samples 9-11 and on an uncoated sample (Sample 12) using the welding parameters detailed in Table 8.

[0116] [Table 8]

[0117] Measurements taken during welding showed that:

[0118] During welding of sample 9, the arc was more stable and the average instantaneous energy was increased by 12% compared to the reference (sample 12). Complete penetration was achieved with sample 9 in contrast to sample 12. During welding of samples 10 and 11, the arc was more stable and the average instantaneous energy was increased by 14% compared to the reference (sample 12). In contrast to sample 12, complete penetration was achieved for samples 10 and 11.

Claims

1. 1. A welding flux comprising a titanate, a nanoparticulate niobium compound selected from niobium oxide, alkali niobates and mixtures thereof, and at least one additional nanoparticulate oxide selected from TiO2, SiO2, ZrO2, Y2O3, Al2O3, MoO3, CrO3, CeO2, La2O3 and mixtures thereof, The proportion of titanate in the dry weight of the welding flux is 45% by weight or more; The proportion of the nanoparticulate niobium compound in the dry weight of the welding flux is between 2 and 30% by weight, A welding flux, wherein the proportion of said additional nanoparticulate oxide in the dry weight of the welding flux is 5-20% by weight.

2. The nanoparticulate niobium compound is NbO, NbO 2 and Nb 2 O 5 2. The welding flux of claim 1, selected from among tungsten carbide, ...

3. The welding flux according to claim 1 or 2, wherein the nanoparticles of the nanoparticulate niobium compound have a size comprised between 5 and 150 nm.

4. The titanate is Na 2 Ti 3 O 7 , NaTiO 3 , K 2 TiO 3 , K 2 Ti 2 O 5 , MgTiO 3 , SrTiO 3 , BaTiO 3 , CaTiO 3 , FeTiO 3 and ZnTiO 4 The welding flux according to any one of claims 1 to 3, selected from among tungsten carbide, ...

5. The welding flux according to any one of claims 1 to 4, wherein the diameter of the titanates is between 1 and 40 μm.

6. The welding flux according to any one of claims 1 to 5, further comprising a solvent.

7. 7. The welding flux of claim 6, comprising 1 to 200 g / L of the nanoparticulate niobium compound.

8. 8. The welding flux according to claim 6 or 7, comprising 100 to 500 g / L of titanate.

9. The welding flux according to any one of claims 6 to 8, further comprising a binder precursor.

10. A method for the manufacture of a pre-coated steel substrate comprising the step of at least partially depositing a welding flux according to any one of claims 1 to 9 onto a steel substrate.

11. 11. A precoated steel substrate obtainable by the method of claim 10, at least partially coated with a precoating comprising a titanate and a nanoparticulate niobium compound selected from among niobium oxide, alkali niobates and mixtures thereof.

12. A method for the manufacture of a welded joint, comprising the following successive steps: I. Providing at least two metal substrates, at least one of which is a pre-coated steel substrate according to claim 11; II. Welding the at least two metal substrates; A method comprising:

13. A flux cored wire comprising the flux according to any one of claims 1 to 5.

14. 14. A method for producing a welded joint comprising arc welding or laser welding to a steel material using the flux cored wire according to claim 13.

15. A method for the manufacture of a welded joint, comprising the following successive steps: I. Providing at least two metal substrates, at least one of which is a steel substrate; II. Applying the welding flux according to any one of claims 1 to 5 onto the at least two metal substrates in front of the welding head simultaneously with the welding of the at least two metal substrates by the welding head; A method comprising:

Citation Information

Patent Citations

  • Active welding flux for high-temperature alloy fusion welding and preparation method thereof

    CN101947703A

  • Nickel-base 625 flux-cored wire suitable for full-position welding

    CN105081620A

  • Flux core for nano-modified boron-containing high-chromium iron hardfacing self-protection flux-cored wire

    CN105269183A

  • Highly abrasion-proof columbium carbide-chromium carbide composite surfacing welding rod

    CN1864910A

  • Modified flux system in cored electrode

    JP2006289492A